2014
DOI: 10.14737/journal.jahp/2014/2.4.51.54
|View full text |Cite
|
Sign up to set email alerts
|

Haematological Traits and Serum Chemistry of Broiler Chicken Fed Bread Waste Based Diets

Abstract: This study was carried out to determine the effects of partial replacement of maize with 50% bread waste meal (BWM) on the haematological traits and serum biochemical indices of broiler chickens. One hundred and twenty days old Anak 2000 broiler chicks were used in an eight week feeding trial; thirty (30) chicks were selected per treatment group and each group was allocated to four treatment diets (1, 2, 3 and 4) with three replicates per treatment in a Completely Randomized Design (CRD). Diet 1, the control d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2019
2019
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 9 publications
0
1
1
Order By: Relevance
“…Only the biochemistry parameter glucose was significantly affected by treatment but did not indicate a dose‐dependent relation with the zinc level or source in feed. The glucose levels identified in all groups are higher than published values (Adekunle and Omoh, ); the reason could be the occurrence of stress in animals before sampling.…”
Section: Assessmentcontrasting
confidence: 73%
“…Only the biochemistry parameter glucose was significantly affected by treatment but did not indicate a dose‐dependent relation with the zinc level or source in feed. The glucose levels identified in all groups are higher than published values (Adekunle and Omoh, ); the reason could be the occurrence of stress in animals before sampling.…”
Section: Assessmentcontrasting
confidence: 73%
“…Blood parameters are also good indicators of the physiological, pathological, and nutritional status of the animal and poultry. Changes in blood parameters can be used to explain the effect of nutritional factors and additives available in the diet on animals or poultry (Adekunle & Omoh, 2014). Al-Kassie (2009) showed that feeding diets were supplemented with oil extracted from thyme to broiler chickens, significantly improved RBCs, Hct, Hb and WBCs counts compared with control basal diet.…”
Section: Statistical Analysesmentioning
confidence: 99%